CpG oligodeoxynucleotide-specific duck TLR21 mediates activation of NF-κB signaling pathway and plays an important role in the host defence of DPV infection. (February 2019) - Cheng, Da; Wu, Xuedong; Jia, Renyong; Wang, Mingshu; Chen, Shun; Liu, Mafeng; Zhu, Dekang; Zhao, Xinxin; Wu, Ying; Yang, Qiao; Zhang, Shaqiu; Zhang, Ling; et al.
Abstract: TLR21 can recognize unmethylated cytosine-phosphate-guanine oligodeoxynucleotides (CpG-ODN) and activates NF-κB immune signaling pathway. However, the function of TLR21 in duck remains largely unclear. Here, the complete duck TLR21 (duTLR21) cDNA was cloned from Cherry Valley duck for the first time, and its immune response was preliminarily studied. Tissue specificity analysis showed duTLR21 was higher expressed in the peripheral blood, spleen, bursa of Fabricius and cecum. The expression of duTLR21 was significantly upregulated after stimulation with CpG-ODN or duck plague virus (DPV), but not Tembusu virus (TMUV), LPS or Poly (I:C). In addition, the transfection of DEF with duTLR21 stimulated by CpG-ODN activated NF-κB, through this signal pathway, the transcription of IL-1β, IL-6 and IFN-α were promoted, whereas knockdown of duTLR21 impaired the transcription of these genes. Furthermore, the overexpression of duTLR21 inhibited the replication of the DPV and the knockdown of duTLR21 by shRNA significantly promoted DPV replication in vitro. Altogether, these results indicate that duTLR21 can be activated by CpG-ODN, which mediates activation of NF-κB signaling pathway, and plays an important role in the host defence of DPV infection.